1988
DOI: 10.1111/j.1471-4159.1988.tb01123.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glutamate and Aspartate Release from Slices of the Hippocampal CA1 Area: Effects of Adenosine and Baclofen

Abstract: Glutamate and/or aspartate is the probable transmitter released from synaptic terminals of the CA3-derived Schaffer collateral, commissural, and ipsilateral associational fibers in area CA1 of the rat hippocampal formation. Slices of the CA1 area were employed to test the effects of adenosine- and gamma-aminobutyrate (GABA)-related compounds on the release of glutamate and aspartate from this projection. Under the conditions of these experiments, the release of glutamate and aspartate evoked by 50 mM K+ was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
64
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(69 citation statements)
references
References 60 publications
4
64
0
1
Order By: Relevance
“…Its action is mediated by adenosine A 1 , A 2A , A 2B , and A 3 receptors. Adenosine modulates neuronal excitability by decreasing neuronal firing [50] and inhibiting the release of neurotransmitters, such as glutamate [4,17], aspartate [6], acetylcholine [34], and γ-aminobutyric acid [3,7]. These effects are mediated by activation of presynaptic adenosine A1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Its action is mediated by adenosine A 1 , A 2A , A 2B , and A 3 receptors. Adenosine modulates neuronal excitability by decreasing neuronal firing [50] and inhibiting the release of neurotransmitters, such as glutamate [4,17], aspartate [6], acetylcholine [34], and γ-aminobutyric acid [3,7]. These effects are mediated by activation of presynaptic adenosine A1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In those pathways, aspartate immunoreactivity was associated with synaptic vesicles to the same degree as glutamate or GABA immunoreactivity. Aspartate is coreleased with glutamate from the Schaffer collateral-commissural and dentate gyrus associationalcommissural pathways in a Ca 2+ -dependent manner [2,3,19] and could serve as a co-transmitter through its selective activation of NMDA receptors [4,22]. However, the mechanism of aspartate release appears to differ in some respects from that of the recognized amino acid transmitters.…”
mentioning
confidence: 99%
“…Adenosine receptors in the CNS have been well characterized in ligand binding studies and have been mapped by autoradiography (Bruns et al, 1980;Goodman et al, 1983). Biochemical experiments have shown that adenosine blocks release of glutamate and aspartate from a number of preparations (Dolphin and Archer, 1983;Corradetti et al, 1984;Fastbom and Fredholm, 1985;Burke and Nadler, 1988), while electrophysiological experiments have shown that adenosine blocks excitatory postsynaptic events (Schubert and Mitzdorf, 1979;Dunwiddie, 1984;Okada and Ozawa, 199 1;Scholz and Miller, 199 1;Yoon and Rothman, 199 1). Adenosine appears to block transmitter release by a presynaptic action limiting calcium influx (Wu et al, 1982;Proctor and Dunwiddie, 1983;Madison et al, 1987;Fredholm and Dunwiddie, 1988), and considerable evidence has been gathered showing that adenosine blocks calcium currents in peripheral (Dolphin et al, 1986;MacDonald et al, 1986) and central neurons (Proctor and Dunwiddie, 1983).…”
mentioning
confidence: 99%